Efetivação da terceira dimensão dos direitos humanos pelas empresas transnacionais no contexto do capitalismo neoliberal - Pissaldo, Ana Paula de Moraes (2016)
This scientific research seeks to draw a parallel between the historical development of capitalism as a mode of production and the possibility of realization of the third dimension of Human Rights, the Solidarity. It thus explores aspects of the globalized economy world and its effects on the human condition, beyond the feasibility study of sustainability in its economic, social and environmental tripod tissue by a typical consumption of liquid modernity in which there is, in fact, the commodification and pricing everything, including the human and biome. The focus of this study lies in the way transnational corporations dictate market rules to have higher revenues than the GDP of many nation-states in installing its operations. So, initially, it is necessary to conceptualize clearly the Transnational Corporation and its law regulation. The central question is the possibility of making the solidarity as a human rights dimension in these transnational corporations, mainly due to the neoliberal moment the economy and world society established. This realization of solidarity through the human development, how they are considered in the global market, as winners, consumers, or just as unable displacement excluded that globalization allows capital holders. The work also addresses the concept of Human Rights and the paths taken by the International Union of nation-states for protection, respect and compensation for violations. Using inductive hypothetical and literature method aims to demonstrate the current state and possible tools to the actual implementation of the third dimension of Human Rights.